The Influence of Service Quality and Price on Indriver Customer Satisfaction (Case Study in the Lembur Sawah Community RW 16 Cimahi, West Java) - Arief Dwi Kurniawan; Yudiyanto Joko Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of service quality and price on Indriver customer satisfaction in the Kp Lembur Sawah Rw 16 Cimahi West Java Community. The background to this research is the importance of understanding factors that influence customer satisfaction in the service industry to improve service quality and pricing strategies. This research uses quantitati ve methods with a survey approach. Data was collected through a questionnaire distributed to the public with a total of 100 respondents who were active users of the service. Data analysis was carried out using the linear regression method to determine the relationship between the independent variables (service quality and price) and the dependent variable (customer satisfaction). The research results show that both service quality and price have a significant influence on customer satisfaction, with service quality having a more dominant influence. These findings provide practical implications for service providers to focus on improving service quality in order to increase customer satisfaction